EFEKTIVITAS VIDEO PEMBELAJARAN TERHADAP PENINGKATAN PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DI SEKOLAH DASAR (Politeknik Kesehatan Kemenkes Bandung, 2021)
Indonesian people experience dental and oral health problems as much as 57.6%. Sweet and sticky foods can cause tooth decay and trigger dental and oral disease if you don't know how to maintain healthy teeth and mouth. One of the efforts to reduce the incidence of caries is to provide education by providing early dental health education to school children, because dental health education is a primary preventive measure before the occurrence of a disease. The purpose of the study was to determine the effectiveness of instructional video media in increasing knowledge about Dental and Oral Health in sixth graders at Pasteur District Elementary School. The research subjects were sixth graders at Pasteur District Elementary School. Sampling technique, total sampling. This study uses a descriptive analysis method with a quantitative approach, to get an overview of the subject's knowledge before and after counseling using learning videos. Using descriptive statistical analysis techniques that present data in the form of frequency distribution tables. The results showed that there was an increase in knowledge of 50%. seen from the pretest given, the average student got a score of 41, and the average posttest score was 82. The results showed that video learning media was effective in increasing knowledge about dental and oral health maintenance in sixth grade elementary school children at Pasteur District Elementary School.